FAKTOR-FAKTOR YANG MEMPENGARUHI PENYAKIT DIARE PADA BALITA DI PUSKESMAS PASAR BARU DENGAN PENDEKATAN ANALISIS REGRESI LOGISTIK - Hasnatul Huda; Atus Amadi Putra (Universitas Muhammadiyah Semarang, 2017)
Diare is a soft or liquid bowel movement that is more frequent than usual. Someof the factors that contribute to the incidence of Diarrhea in infants arematernal education, toddler age, elderly parents, exclusive breastfeeding, toiletcontents, and water sources. The purpose of this study is to see the form oflogistic regression model of factors that occur Diarrhea occurrence in Toddlersin Puskesmas Pasar Baru Bayang Subdistrict Pesisir Selatan Regency, knowwhat is the most severe variable to the occurrence of Diarrhea in Toddlers atPasar Baru Health Center of Bayang District, and for risk factors that occurdiarrhea in Toddlers at Pasar Baru Public Health Center, Bayang District. Theresults showed that factors influencing the incidence of Diarrhea in toddlers atPasar Baru Public Health Center of Bayang Sub District are Toddlers (X2) andExclusive Breast Feeding (X4) with logistic regression model as follows:Nilai odds ratio untuk variabelumurbalita adalah 8,624 dan nilai odds ratiountuk variabel ASI ekslusif sebesar10,110.Keyword:Diare, Logistik, Pesisir Selatan